Towards an understanding of parietal mnemonic processes: some conceptual guideposts - Levy, Daniel A. (Frontiers in Integrative Neuroscience, 2012)
The posterior parietal lobes have been implicated in a range of episodic memory retrieval tasks, but the nature of parietal contributions to remembering remains unclear. In an attempt to identify fruitful avenues of further research, several heuristic questions about parietal-mnemonic activations are considered in light of recent empirical findings: Do such parietal activations reflect memory processes or their contents? Do they precede, follow, or co-occur with retrieval? What can we learn from their pattern of lateralization? Do they index access to episodic representations or the feeling of remembering? Are parietal activations graded by memory strength, quantity of retrieved information, or the type of retrieval? How do memory-related activations map onto functional parcellation of parietal lobes suggested by other cognitive phenomena? Consideration of these questions can promote understanding of the relationship between parietal-mnemonic effects and perceptual, attentional, and action-oriented cognitive processes.